(untitled) (Shaheed Smriti Journal, 2022)
The study examines the effect of tax payers’ awareness and quality of service provided by the local government on tax compliance in Ratnanagar Municipality. The descriptive and explanatory research design has been used to collect primary data through questionnaire. In this study 151 taxpayers, approximately 5% of total population were taken as sample from 16070 households of 16 wards by using convenience sampling method. The data were collected through the five-point Likert scale questionnaire analyzed with the help of SPSS software. The result revealed that tax payers’ awareness and the quality of service provided by local government have a positive and statistically significant relation with tax compliance. In general, increased tax awareness and the provision of quality services by the local government to the tax payers can lead to higher tax compliance.